A model for evaluating eHealth preparedness – a case study approach. Issue 3 (4th May 2020) - Yusif, Salifu; Hafeez-Baig, Abdul; Soar, Jeffrey
Abstract : Purpose: This paper aims to validate an initially developed e-Health readiness assessment model. Design/methodology/approach: The authors thematically analysed an initial qualitative data collected and used the outcome to develop survey instruments for this study. To collect the quantitative data, the authors used the drop and collect survey approach given the research setting. The quantitative data was analysed using factor and regression analyses of SPSS 23 in which hypotheses formulated were tested. Findings: The results suggest that the model [ R 2 = 0.971; F (5, 214) = 1414.303], which is made up of readiness assessment factors (constructs) and measuring tools explain about 97% of the variance of the overall health information technology/e-Health adoption readiness at Komfo Anokye Teaching Hospital. The measuring tools were reliable for assessing the composite variables (constructs): technology readiness; operational resource readiness; organizational and cultural readiness; regulatory and policy readiness; and core readiness, which have significant influence on eHealth adoption readiness assessment.. Originality/value: This study has successfully validated empirically developed eHealth readiness assessment model with complete reliable indicators given that existing eHealth readiness assessment models have not been effective due to a general lack of standard indicators for measuring assessment factors. The study also contributes to the growing research on the adoption of information technology/systems in health-care environment using the Technology–Organization–Environment framework.